ANALISIS JUMLAH LEUKOSIT DAN ERITROSIT PADA URINE LENGKAP PASIEN INFEKSI SALURAN KEMIH (ISK) DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2023 - Dian Magdalena Lase; Rica Vera Br. Tarigan; Paska R. Situmorang (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
Urinary Tract Infection (UTI) is a disease due to infection caused by pathogens that enter the urinary tract, namely the kidneys, ureters, bladder and urethra. The incidence of UTI is still quite common in Indonesia, there are around 90-100 cases per 100,000 data in 2020. Making a diagnosis of UTI, a urinalysis is carried out, namely analyzing a urine sample to calculate the number of leukocytes and erythrocytes in the urine. The purpose of this study is to analyze the total leukocytes and erythrocytes in the complete urine of urinary tract infection (UTI) patients at Santa Elisabeth Hospital Medan 2023. This type of research is a descriptive study with a cross-sectional study design and a sample of 40 people. The results show that most of the patients are female, 26 people (65%) and 14 men (35%). An increase in the number of leukocytes> 4/LP by 40 people (100%) and the number of abnormal erythrocytes (increased) > 2/LP by 37 people (92.5%) and a small proportion of normal erythrocytes 1-2/LP by 3 people (7 ,5%). From the results of the study it can be concluded that women are more at risk due to differences in the anatomy of the female and male urethra and UTI sufferers experience an increase in the number of leukocytes as a marker of inflammation and an increase in the number of erythrocytes due to damage to the glomerular membrane throughout the urinary system.